LEGAL IDENTITY AS SOCIAL IDENTITY: SOME CONCEPTUAL REMARKS - Cahyadi, Antonius (Faculty of Law, Universitas Gadjah Mada, 2024)
Abstract Our widely held assumptions about legal identity often lead us to believe that there is a singular, universally accepted definition. Typically, legal identity is understood through the lens of commonly accepted meaning and reference, often derived from legal identity documents such as the Population Identity Card. However, we must question whether this is the sole form of legal identity documentation and if the concept is solely confined within the realm of public administration, with a strictly formal, neutral, and administrative nature. In this article, the Author will explore and contemplate the meaning of legal identity, starting from normative and ethical perspectives. Our exploration of legal identity will take a multidimensional view, considering the diverse characteristics and elements that constitute it. Abstrak Pengertian manusia terhadap identitas hukum kerap diandaikan begitu saja. Ada kesamaan makna dan ada kesesuaian rujukan dari setiap orang yang berbicara tentang identitas hukum. Dokumen identitas hukum kerap menjadi rujukan utama atas arti dari identitas hukum. Kartu Tanda Penduduk sebagai kartu identitas generik yang dapat mengidentifikasikan seseorang menjadi salah satu contohnya. Tetapi apakah hanya itu saja dokumen identitas hukum? Apakah makna identitas hukum hanya terbatas pada bidang administrasi publik dan bersifat formal administratif saja? Tidak. Artikel ini akan membahas dan merefleksikan makna identitas hukum. Sudut pandang normatif dan etis menjadi titik berangkat penulisan artikel ini. Makna identitas hukum akan dilihat secara multidimensional dengan karakter dan elemen-elemen yang membentuknya.